Implementasi Audit Mutu Internal Pada Perguruan Tinggi Agama - Hamengkubuwono, H (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2017)
Education has become one of the most important instruments in the transformation of human civilization. Thus, the establishment of Islamic Higher Education institution has indicated the responsibility of community on development of this nation. Then, in this modern era, the process of competition among nations has determined by the quality of education. A nation will be known well as strong and advanced nation if the citizen has independence in the culture, economic and politics. Certainly, this matter depended on the role of education side. Thereby, there would be an actualization of human authority in contributing the valuable matters in order to realize a better quality of the nation.